A Pharmacological Review of Five Widely Used Traditional Medicinal Plants for Sedative-Hypnotic Effects in Bangladesh - Biswas, Subir; Sutra Dhar, Ananta; Rahman, Mahbubur; Poly, Khadija A.; Kabir, Imonul (Current Traditional Medicine, 2021)
Medicinal plants are traditionally familiar to treat various physical abnormalities, diseases and illnesses throughout the world A very large number of plant wealth has been offered by the nature for all living organisms, which preserves medicinal excellence. Traditionally in the rural areas, folk medicinal practitioners perform a more ordinary manner of medicine, where medicinal plants constitute the foremost and most often only components of formulations. Geographical and cultural factors of Bangladesh create an abundant source for herbal remedies. Nowadays, several medicinal herbs having their hypnotic and sedative effects are thoroughly used in the treatment of various psychiatric related disorders that include anxiety and insomnia. Sedatives are those types of drugs which diminish the action, inducing a calming and relaxing outcome. Sedatives, in general, produce sleep at higher doses. In recent years, the prevalence of psychiatric disorders which include anxiety and insomnia is rising and therefore different researches are exploring to reveal better medicine to treat these disorders. In this present review, we have performed a comprehensive literature search to find out the five most frequently used medicinal plants with sedative effects for the treatment of various disorders like anxiety and insomnia and their pharmacological activities in scientific researches. The featured plants of this review articles are, Kaempferia galanga, Cleome Rutidosperma, Kalanchoe pinnata, Calotropis gigantea, Scoparia dulcis L. In herbal and traditional medicines, numerous plants are used without their scientific validation and we intend to carry out a literature review in order to find out the effective scientific value of the featured plants. This study will help to affirm the uses of these plants as traditional medicine and the researchers to detect efficient therapeutic drugs according to their pharmacological studies.
Keywords: insomnia